Ions release from fixed orthodontic appliance in two different mouthwashes - Rafeeq, Reem A; Saleem, Alan I; Nissan, Layth MK (Journal of Baghdad College of Dentistry, 2014)
Background: Metal ions can be released from metallic orthodontic appliances due to corrosion in the oral cavity; prophylactic mouthwashes may have an effect on ion release from orthodontic wires. Materials and Methods: Thirty six orthodontic sets of half maxillary fixed appliance with 2 types of arch wires SS and NiTi(Morelli) were constructed and immersed in 2 types of mouthwashes; Claradone (non-fluoridated) and Silver Care (fluoridated) for 28 days at 37Â°C, then the released Ni and Cr ionswere measured using atomic absorption spectrophotometer and compared statistically. Results: Ni ion release was higher from NiTi wire group than SS wire group for both mouthwashes and also was higher for Silver Care group than for Claradone group. While for Cr ion was higher for Silver Care group than for Claradone group, with significant differences for all the groups. Conclusion: Claradone non-fluoridated mouthwash cause less release of Ni and Cr ions release from the orthodontic appliance samples than Silver Care fluoridated mouthwash.